2018
DOI: 10.1186/s12916-018-1177-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between malaria and malnutrition: a systematic literature review

Abstract: BackgroundDespite substantial improvement in the control of malaria and decreased prevalence of malnutrition over the past two decades, both conditions remain heavy burdens that cause hundreds of thousands of deaths in children in resource-poor countries every year. Better understanding of the complex interactions between malaria and malnutrition is crucial for optimally targeting interventions where both conditions co-exist. This systematic review aimed to assess the evidence of the interplay between malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 50 publications
4
63
0
1
Order By: Relevance
“…First, this study further stresses the association between malaria and anaemia in under-fives which various studies have documented [42][43][44][45] extensively. Secondly, this study confirms the complex and inconclusive relationship effect of malnutrition on malaria [46]. There seems to be a vicious cycle between malaria and malnutrition as malaria imposes a heavier burden on malnourished children while malnutrition worsens malaria infection.…”
Section: Discussionsupporting
confidence: 70%
“…First, this study further stresses the association between malaria and anaemia in under-fives which various studies have documented [42][43][44][45] extensively. Secondly, this study confirms the complex and inconclusive relationship effect of malnutrition on malaria [46]. There seems to be a vicious cycle between malaria and malnutrition as malaria imposes a heavier burden on malnourished children while malnutrition worsens malaria infection.…”
Section: Discussionsupporting
confidence: 70%
“…While the common seasonality of malaria and malnutrition has been previously documented [ 8 ], the presence of a biological or immunological interaction between malaria and malnutrition that may encourage a high burden of both diseases remains unclear [ 9 , 10 ]. It has been suggested that malnutrition may predispose children to infection or make it more difficult to recover from infection [ 8 , 11–14 ]; however, the epidemiological evidence is mixed [ 15–25 ].…”
mentioning
confidence: 99%
“…5 A systematic review of studies of the relationship between malaria and malnutrition concluded that the relationship is complex and called for analysis of additional individual patient data of malaria and malnutrition in different settings. 4 Poor nutritional status may predispose children to infection with malaria by modulating immune function, and children with malaria may be predisposed to malnutrition, particularly if they suffer from repeated infection. Conversely, some studies have shown a protective effect of malnutrition against malaria, which may be mediated by iron or other nutritional deficiencies.…”
Section: Introductionmentioning
confidence: 99%